Operational Risk Assesement Tools for Quality Management in Banking Services - Alina Mihaela Dima (Amfiteatru Economic Journal, 2009)
Among all the different types of risks that can affect financial companies, the operational risk can be the most devastating and the most difficult to anticipate. The management of operational risk is a key component of financial and risk management discipline that drives net income results, 2capital management and customer satisfaction. The present paper contains a statistical analysis in order to determine the number of operational errors as quality based services determinants, depending on the number of transactions performed at the branch unit level. Regression model applied to a sample of 418 branches of a major Romanian bank is used to guide the decision taken by the bank, consistent with its priorities of minimizing the risk and enlarging the customer base ensuring high quality services. The analyisis reveals that the model can predict the quality of the transactions based on the number of operational errors. Under Basel II, this could be a very helpful instrument for banks in order to adjust the capital requirement to the losses due to operational errors, predicted by the model.
Keywords: G32; C24; 330; quality management; operational risk; banking services; binary regression model